Economic modeling, analysis, and policy for sustainability - Goswami, Anandajit 1980-; Mishra, Arabinda (A volume in the Advances in Finance, Accounting, and Economics (AFAE) Book Series, 2016)
"This book focuses on interdisciplinary perspectives concerning the social, environmental, and economic spheres of sustainability science, emphasizing economic models, as well as mitigation policies and practices from various regions of the world"-- Provided by publisher.